Graphene-zeolite smart flooring as a catalyst for digital and sustainable transformation in construction: a review - Stephen, Seyi; Aigbavboa, Clinton; Oke, Ayodeji; Idowu, Ayobami; Adekunle, Samuel (Frontiers in Built Environment, 2025)
IntroductionThe integration of advanced materials and digital technologies into construction is essential for achieving energy efficiency and sustainability, with graphene-zeolite smart flooring offering a multifunctional solution to enhance building performance.MethodsA mixed-methods approach was employed, combining quantitative data from a survey of 53 construction professionals with a bibliometric analysis of 179 Scopus-indexed publications using VOSviewer.ResultsThe survey revealed strong industry support for smart materials and technologies that promote energy savings and address environmental concerns, while the bibliometric review identified research clusters in thermal energy storage, nanomaterials, and digital construction systems. Graphene-zeolite composites were found to improve thermal conductivity, enable passive heat storage and release, and enhance air quality through adsorption, with compatibility for integration with artificial intelligence, Internet of Things, and digital twin technologies to support real-time monitoring and predictive maintenance.DiscussionDespite these promising attributes, the absence of empirical testing on thermal performance and long-term durability underscores the need for further validation and field studies. These findings contribute to Sustainable Development Goals (SDG 7, SDG 9, and SDG 13) and highlight future research priorities, including scalable manufacturing, lifecycle assessment, and integration across diverse building typologies to fully realise the potential of graphene-zeolite smart flooring in the built environment.